Pseudomonas rhodesiae HAI-0804 suppresses Pythium damping off and root rot in cucumber by its efficient root colonization promoted by amendment with glutamate - Takeuchi, Kasumi; Ogiso, Masayo; Ota, Arisa; Nishimura, Kentaro; Nishino, Chihiro; Omori, Yasuhiro; Maeda, Mitsunori; Mizui, Ryousuke; Yamanaka, Homare; Ogino, Tomokazu; Seo, Shigemi (Frontiers in Microbiology, 2024)
For full guidelines please refer to Author Guidelines Plant diseases caused by soil-borne fungi and oomycetes significantly reduce yield and quality of many crops in the agricultural systems and are difficult to control. We herein examined Pseudomonas rhodesiae HAI-0804, a bacterial biological control agent that was originally developed for control of bacterial diseases on the surface of vegetables, and assessed its efficacy at controlling soil-borne diseases caused by oomycetes for the practical use of this strain. Strain HAI-0804 did not exhibit detectable antibiotic activity towards Pythium ultimum, a causal agent of damping-off and root rot; however, it effectively protected against Pythium damping-off and root rot in cucumber. Exogenous glutamate enhanced the efficacy of biocontrol, the production of siderophore pyoverdine, root colonization in cucumber plants, and the ratio of biofilm formation to planktonic cells. The epiphytic fitness of strain HAI-0804 appears to contribute to plant protection efficacy against a broad spectrum of pathogens for both above-ground plant parts and the rhizosphere.